Vagal nerve stimulation activates vagal afferent fibers that reduce cardiac efferent parasympathetic effects - Yamakawa, Kentaro (Am J Physiol Heart Circ Physiol, 2015)
Vagal nerve stimulation (VNS) has been shown to have antiarrhythmic effects, but many of these benefits were demonstrated in the setting of vagal nerve decentralization. The purpose of this study was to evaluate the role of afferent fiber activation during VNS on efferent control of cardiac hemodynamic and electrophysiological parameters. In 37 pigs a 56-electrode sock was placed over the ventricles to record local activation recovery intervals (ARIs), a surrogate of action potential duration. In 12 of 37 animals atropine was given systemically. Right and left VNS were performed under six conditions: both vagal trunks intact (n = 25), ipsilateral right (n = 11), ipsilateral left (n = 14), contralateral right (n = 7), contralateral left (n = 10), and bilateral (n = 25) vagal nerve transection (VNTx). Unilateral VNTx significantly affected heart rate, PR interval, Tau, and global ARIs. Right VNS after ipsilateral VNTx had augmented effects on hemodynamic parameters and increase in ARI, while subsequent bilateral VNTx did not significantly modify this effect (%change in ARI in intact condition 2.2 ± 0.9% vs. ipsilateral VNTx 5.3 ± 1.7% and bilateral VNTx 5.3 ± 0.8%, P < 0.05). Left VNS after left VNTx tended to increase its effects on hemodynamics and ARI response (P = 0.07), but only after bilateral VNTx did these changes reach significance (intact 1.1 ± 0.5% vs. ipsilateral VNTx 3.6 ± 0.7% and bilateral VNTx 6.6 ± 1.6%, P < 0.05 vs. intact). Contralateral VNTx did not modify VNS response. The effect of atropine on ventricular ARI was similar to bilateral VNTx. We found that VNS activates afferent fibers in the ipsilateral vagal nerve, which reflexively inhibit cardiac parasympathetic efferent electrophysiological and hemodynamic effects.